2020
DOI: 10.1039/d0na00733a
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of silver nanoparticle dissolution under physiological conditions

Abstract: Upon dissolution of silver nanoparticles, silver ions are released into the environment, which are known to induce adverse effects. However, since dissolution studies are predominantly performed in water and/or at...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Silver nanoparticles (AgNPs) exhibit unique and interesting properties, including notable physiological characteristics and broad applicability [64]. In this work, AgNPs were prepared via a solution process in a very short time, and were well characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver nanoparticles (AgNPs) exhibit unique and interesting properties, including notable physiological characteristics and broad applicability [64]. In this work, AgNPs were prepared via a solution process in a very short time, and were well characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports showed that the cytotoxicity of cancer cells is greatly affected and is responsible for the regulation of cancer cell growth [65,66]. Despite this, several other factors were also affected, such as the shape of the nanostructures, size, composition of cells, culture medium, doses of nanostructures, and pH [64,66]. The morphological changes after the interaction of different concentrations (2, 5, 10, 25, 50, 100 µL/mL) of AgNPs with cancer cells were observed using an inverted microscope after a 24 h incubation period, and cell death was observed.…”
Section: Discussionmentioning
confidence: 99%
“…21,30 Upon contact with physiological fluids or physical barriers, via different administration routes, NPs may undergo a process of aggregation and/or dissolution. 31,32 In addition, the different constitution of physiological fluids (e.g., proteins, lipids and electrolytes) including blood, respiratory and gastrointestinal mucus, and tear fluid might affect NP properties and thus cell-NP interactions. [33][34][35] Inhalation has been used for the administration of nanomaterials to treat lung diseases or for systemic delivery.…”
Section: Cellular Uptake Mechanisms Of Npsmentioning
confidence: 99%
“…However, the preparation of highly reproducible monodisperse AgNPs is much more difficult than for gold nanoparticles (AuNPs) due to the higher reactivity of Ag atoms than Au atoms [ 20 ]. In addition, it has been reported in the literature that AgNPs undergo dissolution in aqueous solutions, which limits their applicability as SERS substrates, especially for environmental samples [ 21 ]. Based on this, despite the larger scattering contribution and thus higher SERS enhancement factor of AgNPs compared to AuNPs, this study was conducted utilizing 14 nm and 46 nm spherical AuNPs.…”
Section: Introductionmentioning
confidence: 99%